The impact of Brexit on the stock markets of the greater China region - Lucía Morales; Bernadette Andréosso-O'Callaghan (International Journal of Financial Studies, 2018)
An examination of Brexit and its initial impact on the main stock markets in the Greater China Region (GCR) was conducted using augmented market models that integrate Economic Policy Uncertainty (EPU) and implied volatility (VIX). The results do not seem to align with research in the field that has suggested that the EPU index helps to identify if market participants are reacting to political events. The main research findings suggest that Brexit does not appear to have an impact on the performance of market returns in the region and the influence of economic policy uncertainty in the GCR appears to be insignificant, except for Hong Kong. Overall, China's stock markets do not seem to be panicking and overreacting to unfolding events in the UK, and market instability in the region appears to be more associated with global and regional events that are better captured by the VIX index.
Keywords: F36; F65; G15; 330; Brexit; rising China; globalisation; stock markets; Economic Policy Uncertainty; political turbulences